Dynamin Rings: Not Just for Fission. (19th September 2013) - Sever, Sanja; Chang, Joann; Gu, Changkyu
Abstract : Dynamin is essential for regulation of actin cytoskeleton, though its mode of action is currently unknown. Recently, direct dynamin–actin interactions and actin‐dependent dynamin oligomerization have been identified. Actin‐dependent dynamin oligomerization has been linked to formation of free barbed ends, and thus actin polymerization in vitro . Here we discuss the possibility that actin‐dependent dynamin oligomerization plays a major role in regulating the actin cytoskeleton via its effect on actin polymerization at distinct sites in the cell. Abstract : The GTPase dynamin has captivated researchers for over two decades, even managing to establish its own research field. Dynamin's allure is partly due to its unusual biochemical properties as well as its essential role in multiple cellular processes, which include the regulation of clathrin‐mediated endocytosis and of actin cytoskeleton. On the basis of the classic model, dynamin oligomerization into higher order oligomers such as rings and helices directly executes the final fission reaction in endocytosis, which results in the generation of clathrin‐coated vesicles. Dynamin's role in the regulation of actin cytoskeleton is mostly explained by its interactions with a number of actin‐binding and ‐regulating proteins; however, the molecular mechanism of dynamin's action continues to elude us. Recent insights into the mechanism and role of dynamin oligomerization in the regulation of actin polymerization point to a novel role for dynamin oligomerization in the cell .